2014
DOI: 10.3390/su6107242
|View full text |Cite
|
Sign up to set email alerts
|

Is There Any Evidence on the Existence of an Environmental Taxation Kuznets Curve? The Case of European Countries under Their Rule of Law Enforcement

Abstract: Abstract:The paper gives new insights into the environmental taxation policy, demonstrating the existence of an inverse U-shaped relationship between environmental taxation and income in European countries. Our findings reveal this relationship to be influenced by enforcement of the rule of law, which contributes to shifting the turning point on the curve to lower income levels. We show that former transition economies have not reached the turning point due to weak institutions. To achieve the goal of sustaina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 43 publications
2
16
0
Order By: Relevance
“…Therefore, the indirect effect of patent through economic growth on environmental pollution emissions can be considered. Castiglione, Infante, and Smirnova [36] conducted an analysis on both the direct effect and indirect effect of the independent variable on the dependent variable. They analyzed the indirect effect of the rule of law through increasing economic growth on the environmental tax.…”
Section: Methodsmentioning
confidence: 99%
“…Therefore, the indirect effect of patent through economic growth on environmental pollution emissions can be considered. Castiglione, Infante, and Smirnova [36] conducted an analysis on both the direct effect and indirect effect of the independent variable on the dependent variable. They analyzed the indirect effect of the rule of law through increasing economic growth on the environmental tax.…”
Section: Methodsmentioning
confidence: 99%
“…A few studies make an effort to analyse the ET policy instruments and identify factors crucial for its efficacy (Anger et al 2006;Bovenberg and de Mooij 1997;Castiglione et al 2014;Ekins and Barker 2001;Muller and Sterner 2006;Ward and Cao 2012). In the light of these studies, the most explored determinants of ET can be identified.…”
Section: Environmental Taxation and Economic Growthmentioning
confidence: 99%
“…Obviously, the quality of governance is closely related to its enforcement. Institutions such as property rights, legal origins, and democracy have been shown to have an important impact on environmental quality and policy (Cole 2007;Damania et al 2003;Pellegrini and Gerlagh 2006) and, consequently, on ET (Castiglione et al 2014). From the environmental perspective, the institution of the rule of law is of major importance since it reflects the supremacy of law and the quality of the institutional context itself.…”
Section: Rule Of Law Ict and Importationmentioning
confidence: 99%
“…Most policies regarding the environmental protection were introduced in Europe at the end of 1998-1999. Where the rule of law was strong and policies were properly set, the volume of environmental taxation first increased and then decreased as a consequence of the effectiveness of environmental policies [1].…”
Section: Introductionmentioning
confidence: 99%
“…Former transition countries have not yet reached the turning point of the U-curve, and this probably reflects less stringent institutional context [16] for a full implementation of the environmental policies. In the European countries where environmental taxation has started to decrease, this is mainly due to institutional reforms [1].…”
Section: Introductionmentioning
confidence: 99%